2008
DOI: 10.1044/0161-1461(2008/014)
|View full text |Cite
|
Sign up to set email alerts
|

Noun Phrase Elaboration in Children’s Spoken Stories

Abstract: There are important developmental changes in noun phrase elaboration in the elementary school years as children learn to manage narrative contexts. Even within picture tasks, variations in visual depiction can affect the use of elaborated noun phrases (ENPs), with more descriptive language more likely to occur in narratives based on a single picture fantasy context than on a realistic picture sequence context. Performance expectations for types of ENPs within these contexts are provided. These findings will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
1
27
0
2
Order By: Relevance
“…These indices have been used widely in previous research to characterize the narrative abilities of young children (e.g., Eisenberg et al, 2008;Justice et al, 2006;Kay-Raining Bird, Cleave, White, Pike, & Helmkay, 2008;Scott & Windsor, 2000). Grammatical complexity refers to how children construct sentences in both simple and complex ways to express ideas within stories.…”
Section: Narrative Transcription and Codingmentioning
confidence: 98%
“…These indices have been used widely in previous research to characterize the narrative abilities of young children (e.g., Eisenberg et al, 2008;Justice et al, 2006;Kay-Raining Bird, Cleave, White, Pike, & Helmkay, 2008;Scott & Windsor, 2000). Grammatical complexity refers to how children construct sentences in both simple and complex ways to express ideas within stories.…”
Section: Narrative Transcription and Codingmentioning
confidence: 98%
“…For example, a child constructing a creative play theme said, ''This is a power pig'' as he placed the pig in the barn (Family 14 1 ). In the limited literature on school-age children's use of adjectives, Maloney and Hopkins (1973) reported a positive association between creativity ratings of stories and the number of adjectives employed (see also Eisenberg et al, 2008). In terms of pretense in sibling play, Howe and Bruno (2010) reported an association between adjective use by 5-year-old younger siblings and creative play themes; patterns for older siblings were more mixed.…”
Section: Pretense Asmentioning
confidence: 91%
“…For example, Maloney and Hopkins (1973) reported that the written narratives of school-age children that included more adjectives were judged as being more creative compared to those with fewer adjectives. School-age children also produced narratives with more descriptive language in response to a picture depicting a fantasy scenario compared to a realistic scenario (Eisenberg et al, 2008).…”
Section: Creativitymentioning
confidence: 99%
“…In maternal presence the younger siblings' total adjective use was also associated with sibling collaboration. We have argued that the use of adjectives demonstrates an ability to employ descriptive and creative language during play interactions (Eisenberg et al, 2008;Maloney & Hopkins, 1973). In particular, examining the number of different adjectives provides a measure of the breadth of children's ability to describe and enrich their linguistic environment (Blackwell, 2005), in this case their pretense communications.…”
Section: Pretense Collaboration and Creativity Within Mother Absentmentioning
confidence: 99%